Mature T‐ and NK‐cell non‐Hodgkin lymphoma in children and young adolescents. (15th March 2016) - Pillai, Vinodh; Tallarico, Michael; Bishop, Michael R.; Lim, Megan S.
Summary: Mature T/Natural killer (NK)‐cell neoplasms of children and the young adolescent population exhibit higher prevalence in Central and South American and Asian populations and many are associated with Epstein‐Barr virus (EBV). They are represented in large part by extranodal T/NK cell lymphomas‐ nasal‐type or extra nasal‐type, chronic lymphoproliferative disorders of T/NK cells or chronic active EBV disease, systemic EBV‐positive lymphoproliferative disorders of childhood, hydroa vacciniforme‐like lymphoma, hepatosplenic T‐cell lymphoma and primary cutaneous gamma/delta T‐cell lymphoma among others. Many T/NK cell neoplasms in this age group are derived from cells of the innate immune system, in contrast to adults where they are predominantly from the adaptive immune system. The genetic basis of T/NK cell lymphomas in children and young adolescents remains largely unknown. Anthracycline‐based regimens and haematopoietic stem cell transplants (allogeneic and autologous) are current treatment modalities, however it is anticipated that novel targeted therapeutic agents will be available in the near future.